The impact of government debt on output, private investment and human capital stock in Malaysia - Hajian, Hoda; Mohamed, Azali; Habibullah, Muzafar Shah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper mainly aims to examine the effect of government debt on real output per capita in a successful developing economy of Malaysia during 1985-2014 period. Using Vector Error Correction modeling (VECM) and employing Generalized Impulse Response (GIR) tool, dynamic response of output per capita to a shock to government debt is obtained. Using the same model, the effect of government debt on economic growth factors, namely, private investment and human capital are also examined. The impulse response result based on VECM model shows that using this sample on average debt does not significantly influence output per capita and private investment although, the later shows negative response. However, human capital positively respond to a debt shock. Overall, this result did not find evidence for crowding out effect of government debt. In other words, the result provide some support for prudent debt management in Malaysia in the past. However, wisely use of government sources is always important. Moreover, excessive borrowing is not advised as it could negate positive effects and jeopardize debt sustainability.